Antimicrobial potential of passion fruit (Passiflora edulis) leaves against escherichia coli,staphylococcus aureus, aspergillus niger and candida utilis. - Rodil, Joan Camille E. 4 0 16; 5 (2007)
u
Thesis : (B.S. Biology) - Pamantasan ng Lungsod ng Maynila, 2007.
Keywords: 2 -- 0; 6; 20; 20; 2